What do needle and syringe programs do?: an assemblic account of staff-client relationships at needle syringe programs - Yates, Ken (Palgrave pivot, 2023)
This book explores the lived experiences of people who interact with needle and syringe program services in Western Sydney, Australia, including participants and industry workers. It locates the research within the wider context of harm reduction and drug policies. It addresses the question "what do needle and syringe programs do?" and seeks to unpack the agency of human and non-human factors to consider the ‘more than human’ effects of these programmes. Alongside a critical materialist perspective used to interpret the empirical findings, the book demonstrates that needle and syringe programs create new possibilities for engaging with the world by changing the material conditions of illicit drug consumption. It draws on the conceptual contributions of post-humanist thinking from assemblage theory, actor-network theory, and cognate scholarship. Consideration is given to transferable findings and insights for international contexts. The book speaks to scholars and postgraduate students in the areas such as sociology, criminology, social work, critical public health, cultural studies, and related fields. Ken Yates is a sociologist and criminologist at Western Sydney University, Australia. He is interested in the interrelations between deviance, criminality, health, harm reduction, drug use, and neoliberal capitalism. He has taught qualitative research methods and criminology to undergraduates, crime prevention perspectives to police and local government, and provided research assistance to non-government mental health and AOD service providers. Ken has published research concerning harm reduction services, trust, inter-agency collaboration in child and family services, qualitative methods in harm reduction, and attitudes to technology.